Effect of chewing gum on postoperative ileus reduction and improving gastrointestinal motility in postoperative abdominal patients at Jayapura city hospital - Rohmani Rohmani; Hugo Kingson Borneo (Institute of Computer Science (IOCS), 2022)
Research Objective knowing the effect of chewing gum to prevent postoperative ileus in postoperative abdominal patients. Research Methods: this type of research is quantitative research with a quasi-experimental pre and post with a control approach with a total sample of 30 people with. The method of collecting accidental sampling is because the samples in Jayapura city for abdominal surgery are still limited. The tests used are Wilcoxon test and man whitney. Results: the results of the univariate analysis found that male respondents amounted to 20 respondents (66.7%) and women respondents amounted to 10 respondents (33.3). The age of the most respondents was between 16 - 35 years old was 19 respondents (63.3%) and the least was between the ages of 56 - 75 years old was 2 respondents (6.7%). Wilcoxon test results obtained p-value values of 0.001 < 0.005 meaning that there is an effect of chewing gum on improving intestinal motility of patients post-abdominal surgery. Conclusion: there is an effect of chewing gum on postoperative ileus decrease and improvement of gastrointestinal motility in Post Abdominal Surgery patients.